Decreased nasal nitric oxide in children with isolated midline neuroanatomical defects: a possible indicator of ciliary dysfunction?. (3rd June 2015) - Goez, H; Scott, O; Al-Jabri, B; Prowse, M; Beaudoin, W; Hall, S; Mehta, V; Amirav, I
Abstract : Background: Ciliary mutations cause multi-system disorders, often involving the CNS. We set to evaluate the prevalence of ciliary dysfunction in children with isolated neuroanatomical defects, by measuring nasal nitric oxide (nNO), a screening test for Primary Ciliary Dyskinesia (PCD). Study design: We measured nNO levels of 26 children with congenital midline CNS defects. We evaluated the effect of age, gender, and anomaly (brain, spinal cord, or combined) on measurements. We compared our results to the previously established normal range (153.6-509.9 nL/min), and to the cutoff for PCD (77 nL/min). Results: The range for nNO in our cohort was 56.5-334.7 nL/min, with age, gender, and anomaly not having a significant effect. The overall mean, 217.7 nL/min, was significantly lower than that of normal children, 314.51 nL/min (p<0.01). Four subjects (15.4%) had nNO levels below the lower end of normal, with two (7.7%) having values fitting the cutoff for PCD. Conclusions: We report an association between ciliary dysfunction and isolated midline neuroanatomical defects, not in context of any known syndrome. This suggests that genes causing isolated CNS defects, may be implied in the function of cilia. Longitudinal studies are required to investigate whether children with abnormal measurements suffer from any respiratory sequelae.